For the polynomial below, 3 is a zero.

f(x)= 3x^3 - 10x^2 + x + 6

Express f(x) as a product of linear factors.

Use fractions or square roots, not decimals.

Thank you for the opportunity to help you with your question!

since 3 is a zero,x-3 = 0so, f(x)= 3x^3 - 10x^2 + x + 6= 3x^2(x-3) - x(x-3) -2 (x-3)= (3x^2 - x -2)(x-3)=(3x^2 -3x +2x -2)(x-3)=[3x(x-1)+2(x-1)](x-3)=(3x+2)(x-1)(x-3) (Answer)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up